Cortisol, Testosterone, and Alpha-Amylase in Psychopathy - Glenn, Andrea L (2011)
A recently developed theory suggests that imbalances in hormone systems may contribute to psychopathy (van Honk & Schutter, 2006). Researchers have begun to emphasize the interconnectedness of hormone systems, and recommend examining multiple systems simultaneously in order to examine potential interactions. Very few studies have examined the role of hormones in psychopathy and results have been mixed, possibly due to the examination of only one hormone at a time. In a sample of 178 adults from the community demonstrating a wide range of psychopathy scores, I examine the relationship between psychopathy and two hormones and one enzyme that have been theoretically linked to psychopathy – cortisol, testosterone, and alpha-amylase. In Section 1, I focus on cortisol and testosterone – the end products of two hormonal axes that work together to maintain an appropriate balance between withdrawing in the presence of fearful or threatening stimuli, and approaching in the presence of reward – the hypothalamus-pituitary-adrenal (HPA) axis and the hypothalamus-pituitary-gonadal (HPG) axis. Psychopathy is associated with an apparent imbalance in these processes, as it is characterized by reduced fearfulness, insensitivity to punishment, reward-seeking, and aggression (Hare, 2003). Psychopathy was not associated with cortisol or testosterone measures individually, but was associated with the ratio between baseline testosterone levels and cortisol reactivity to a stressor. In Section 2, I focus on cortisol and alpha-amylase – indicators of the two primary components of the stress response system – the HPA axis and the sympathetic nervous system. Researchers have hypothesized that deficits in this system contribute to the fearlessness and insensitivity to punishment observed in psychopathy, but the relative contribution of the two components, or how they may interact, has not been explored. Psychopathy was not associated with cortisol or alpha-amylase measures individually. However, an interaction was observed indicating that at high levels of alpha-amylase, cortisol was negatively associated with psychopathy. Overall, these results support the hypothesis that psychopathy is associated with an altered balance between highly interconnected hormone systems, and emphasize the importance of examining multiple systems simultaneously